CEDAW AND THE RIGHTS OF KINSHIP IN ISLAMIC FAMILY LAW - Fuad, Ahmad Masfuful (Islamic University of Indonesia, 2015)
The following article traces the issues of Human Rights (HAM) has always been the center of attention, including in relation to family law in Islam. The principles of equality, equal rights, and equal position for the relationship of husband and wife become a topic of interest for many people. The birth of the CEDAW (Convention on the Elimination of All Forms of Discrimination Against Women), proves that the international community to pay more attention to this issue. Islam, as a religion which contains a comprehensive way of life certainly had her cover of this issue through the principles of Islamic family, because Islam was very attentive to the importance of the institution of family as one unit in society. The result of this article has been revealed that the basic principles of Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) for instances equality, equal position and equal rights in accordance with the principles of Islamic law. Keywords : Islamic Family Law, Human Rights, CEDAW, Kinship.